SOSIALISASI PEMBENAHAN LAPORAN KEUANGAN BADAN USAHA MILIK DESA (BUMDes) DESA BATUMARTA II KABUPATEN OKU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
The purpose of this Community Service (PPM) activity is to describe how to make financial reports in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This is in view of the importance of knowledge and insight of the managers of Village Owned Enterprises (BUMDes) in Batumarta II Village regarding financial reports. Through this socialization, it is hoped that BUMDes managers can increase their knowledge, insight and understanding as well as experience so that they have good abilities in preparing financial reports in accordance with established standards. This activity was attended by the manager of BUMDes in Batumarta II Village. This Community Service Activity (PPM) was held on February 22, 2020 in Batumarta II Village. The material presented was about